Consumer reactions to rebranding strategy in emerging markets: evidence from the tunisian retail sector and the “promogro” to “MG maxi” transition - Ahmed Kannou; Kaouther Saied Ben Rached (Cogent Business & Management)
This article examines how consumers evaluate retailer rebranding strategies, with a specific focus on the rebranding of “Promogro” to “MG Maxi” in Tunisia. The study addresses the need to understand consumer reactions to brand transitions, particularly in a competitive retail market. A quantitative research approach was employed, utilizing survey data collected from a sample of 351 Tunisian consumers, which was analyzed using structural equation modelling (SEM) to test the main hypotheses and assess the impact of key variables on consumer evaluation. The findings reveal a negative correlation between customers’ attachment to the old retailer brand and their attitudes toward the rebranding process. Furthermore, retailer brand perceptions act as a competitive mediator between attitudes toward rebranding and consumers’ intentions to revisit. The results also indicate that the perceived similarity of the new retailer brand positively moderates the relationship between consumer attachment and perceptions of the renovated retailer brand. Specifically, strong attachment to the old brand leads to more favorable perceptions of the new brand when similarity is high. This study provides insights for practitioners on key success factors for consumer acceptance during rebranding, offering practical guidance for a seamless transition in the Tunisian market.